ERCC1 Protein Expression Is Associated with Differential Survival in Oropharyngeal Head and Neck Squamous Cell Carcinoma. Issue 4 (11th July 2013) - Patel, Mihir R.; Zhao, Ni; Ang, Mei‐Kim; Stadler, Michael E.; Fritchie, Karen; Weissler, Mark C.; Zanation, Adam M.; Harris, Stephen L.; Funkhouser, William K.; Olshan, Andrew F.; Shores, Carol G.; Hayes, D. Neil
Abstract : Objective: To investigate ERCC1 protein expression and its relationship to clinical factors and treatment outcomes in patients with head and neck squamous cell carcinoma (HNSCC). Design: Case series. Setting: Tertiary care academic center. Subjects: One hundred and seventy‐six patients diagnosed with HNSCC and treated with intent to cure between 2002 and 2008 were analyzed with respect to clinical data and tumor pathology. Main Outcome Measures: Tissue microarrays were constructed from tumor blocks and immunohistochemical staining for ERCC1 performed. ERCC1 expression status was dichotomized into high and low using the Allred score. Clinical characteristics of patients with high versus low ERCC1 expression were compared. Distributions of overall survival (OS) and progression‐free survival (PFS) were analyzed using the Kaplan‐Meier method. Results: Of 176 patients, ERCC1 showed baseline nuclear staining in 148 patients (84.1%). Lower staining intensity ERCC1 expression was prominent in parabasal cells in the lower half of the epithelium, while at high staining intensity, ERCC1 expression was present throughout the epithelium. The median H‐score was 50. No significant differences in age, gender, smoking status, tumor site, or stage were seen between the high and low ERCC1 expression groups. Expression of ERCC1 stratified by tumor site correlates with OS. Patients with oropharyngeal HNSCC and high ERCC1 expression (H‐score > 120) were more likely to survive ( P <. 01) and remain disease free when compared to non‐oropharyngeal squamous cell carcinoma (SCCa) patients with high ERCC1 expression despite treatment modality and human papillomavirus virus (HPV) status. Conclusion: Patients with oropharyngeal SCCa and high ERCC1 expression may have better outcomes despite HPV status.